Mutation Screening of the Krüppel-like Factor 1 Gene in Individuals With Increased Fetal Hemoglobin Referred for Hemoglobinopathy Investigation in South of Iran. Issue 3 (April 2018) - Hamid, Mohammad; Ershadi Oskouei, Sanaz; Shariati, Gholamreza; Babaei, Esmaeil; Galehdari, Hamid; Saberi, Alihossein; Sedaghat, Alireza
Abstract : Background: Any mutation in the Krüppel-like factor 1 ( KLF1 ) gene may interfere with its proper related function in the erythropoiesis process and lead to alterations in proper activation of its downstream protein through globin switching, which results in an increase in fetal hemoglobin (HbF). This study aimed to investigate whether KLF1 mutation can associate with high level of HbF in individuals with increased fetal hemoglobin referred for screening of hemoglobinopathies in south of Iran. Materials and Methods: The human KLF1 gene was amplified via the polymerase chain reaction procedure, and sequencing was used to determine any mutation in these patients. Moreover, Xmn I polymorphisms in the position of −158 of γ-globin gene promoter were analyzed in all patients by polymerase chain reaction restriction fragment length polymorphism. Result: Analysis of sequencing revealed a missense mutation in the KLF1 gene, p.Ser102Pro (c.304T>C), which was detectable in 10 of 23 cases with elevated HbF level. This mutation was only detected in individuals who had a HbF level between 3.1% and 25.6%. Statistical analysis showed that the frequency of C allele is significantly correlated with a high level of HbF ( P <0.05). The allele frequency of positive result of Xmn I polymorphism in individuals with increased HbF level was also significant, which showed an association with increased HbF level ( P <0.05). Conclusions: To the best of our knowledge, this is the first report of p.Ser102Pro (c.304T>C) in the KLF1 gene in β-thalassemia patients with increased level of fetal hemoglobin. According to statistical results of p.Ser102Pro mutation and Xmn I polymorphism, it has been strongly suggested that both polymorphisms have an association with increased HbF samples. These nucleotide changes alone may not be the only elements raising the level of HbF, and other regulatory and modifying factors also play a role in HbF production.